Energy Transition and Renewable Energy Industry: A Bibliometric Analysis of Literature - Ikhmim, Jihane; Hda, Mounia; Benmiloud, Najlae; Ikhmim, Maroine (International Journal of Energy Economics and Policy, 2025)
The energy transition has emerged as a critical response to climate crises, fossil fuel dependency, and sustainability imperatives. This study explores the intersection between the energy transition and the renewable energy industry, emphasizing the role of RE technology integration into industrial value chains. This article aims to conduct a literature review to map scientific literature on the integration of renewable energy technologies within industrial value chains. It identifies key research themes, methodological trends, and the economic, technological, and policy challenges shaping this domain. This study combines bibliometric analysis with qualitative content analysis, accessed through leading databases. The selection process, through clear inclusion and exclusion criteria, used the PRISMA 2023 protocol. Through VOSviewer, Bibliometric mapping identified significant authorship and thematic clusters patterns, with NVivo enabling consideration of conceptual relationships and dominant research themes across literature. The review identifies five dominant thematic clusters: renewable energy & energy transition, carbon neutrality, supply chain economics, technological innovation, and public policy. It highlights increasing interdisciplinarity, a convergence of qualitative and modeling approaches, and the need for deeper exploration of governance and social impacts. The study contributes a structured mapping of the RE-industrial integration literature and provides a valuable foundation for future research.